1995
DOI: 10.1289/ehp.103-1519226
|View full text |Cite
|
Sign up to set email alerts
|

Biological monitoring of polycyclic aromatic hydrocarbon exposure in a highly polluted area of Poland.

Abstract: Air pollution in Poland and particularly in Silesia is among the worst in Europe. Many coal mines and coke oven plants are located in this area, representing a major source of carcinogenic polycyclic aromatic hydrocarbons (PAHs). We quantitated the PAH exposure level in air samples using personal sampling devices, collected urine samples from the same individuals, and measured 1-hydroxypyrene with high performance liquid chromatography. Samples were collected twice, once in February and once in September. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Urinary 1-OHP, a metabolite of PAHs, has been shown to be an indicator of both uptake of pyrene from foods and exposure to exogenous PAHs ( Jongeneelen 2001 ; Kanoh et al 1993 ; Ovrebo et al 1995 ). Moreover, the level of urinary 1-OHP has been shown to be correlated with genotoxic effects in coke oven workers as determined by a number of assays, including micronuclei frequency and DNA damage measured by sister-chromatid exchange and comet assays ( Siwinska et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary 1-OHP, a metabolite of PAHs, has been shown to be an indicator of both uptake of pyrene from foods and exposure to exogenous PAHs ( Jongeneelen 2001 ; Kanoh et al 1993 ; Ovrebo et al 1995 ). Moreover, the level of urinary 1-OHP has been shown to be correlated with genotoxic effects in coke oven workers as determined by a number of assays, including micronuclei frequency and DNA damage measured by sister-chromatid exchange and comet assays ( Siwinska et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure may be monitored through environmental samples and the use of biomarkers of exposure. [13][14][15][16] PAH exposure is a problem not confined specifically to Asia, yet it can be observed that it is relatively pronounced in Bangkok when compared to many other cities in the same as well as in other parts of the world. 11,[17][18][19][20][21] One of the assumptions in the studies conducted in our laboratory is that since PAH's are traffic-related air pollutants and are normally particle-associated, their concentrations should be highest near the source, that is, on the roads, and that the people most at risk are those who spend significant portions of their day directly at or very near these sources (TABLE 1).…”
Section: Pahsmentioning
confidence: 99%
“…There is evidence that 1-OHP may correlate better with relatively higher occupational exposures rather than environmental exposures. 15,16 PAH-DNA adducts represent both biomarkers of exposure and biomarkers of biologically effective dose since PAHs are metabolized to electrophilic intermediates, which bind to cellular macromolecules, such as DNA and proteins to form adducts. The formation of DNA adducts is believed to be the first step in the initiation of carcinogenesis.…”
Section: Pahsmentioning
confidence: 99%
“…석탄광산이 349개, 금속광산이 988개, 비금속광산이 699 개 등 총 2,036개 광산이 전국적으로 분포하고 있는 것으로 알려져 있다 (Jung et al, 2010 (Choi et al, 2010;Yun et al, 2011;Jang et al, 2011 (Cho et al, 1996;Kim et al, 1997;Min et al, 1997;Kim et al, 1998;Min et al, 2005;Lee et al, 2006;Park et al, 2007) (Ovrebo et al, 1995;Micic et al, 2007;Pies et al, 2007;Achten and Hofmann, 2009;Bandowe et al, 2010 (Zuo et al, 2007;Achten and Hofmann, 2009;Chen et al, 2011 (Choi et al, 2010;Yun et al, 2011;Jang et al, 2011) (Ovrebo et al, 1995;Micic et al, 2007;Pies et al, 2007;Achten and Hofmann, 2009;Bandowe et al, 2010)…”
Section: 서 론unclassified